The Total Antioxidant Levels, Amino Acids, Vitamins, Flavonoids and Phenolics Profile of Persea americana Using HPLC - Yakubu, Ojochenemi Ejeh; Danjuma, Janya; Jankada, Patience Audu (Darul Yasin Al Sys, 2024)
This research investigated the antioxidant levels, flavonoids and phenolics, amino acid and vitamin profile of P. americana seed methanol extract. Fresh fruits of P. americana were procured from Baissa in Taraba State. The fruits were cut open and the seed removed, washed and sliced. The plant material was air dried at room temperature after which it was pulverized and extraction was carried out using methanol for 72 hours. Extract was subjected to total antioxidant test using DPPH by serial dilution. Different portions of the extract were used to analyze for total flavonoid content and total phenolics content using aluminium chloride and folin-ciocalteu respectively. Furthermore, a portion of the extract was used to analyze for amino acid, vitamin and flavonoids and phenolics profile. The result reveals that the portion antioxidant activity increase with concentration. The portion with 1000µg/1000mL had over 80% which was the highest inhibition percentage in the series. Total flavonoid was found to be 39.88 ± 0.44 while the total phenolic content was seen to be 35.84 ± 4.30. Quercetin and chlorogenic acid were seen to be present for HPLC analysis of flavonoids and phenolics profile to be 15.8% and 84.2% respectively. The result for vitamin profile reveals that three vitamins were detected: vitamins K, B1 and B3 at 0.1%, 20.4% and 79.5% respectively. The amino acid present include asparagine, threonine, serine and aspartic acid with 1.1%, 13.9%, 10.4 and 74.6% abundance respectively. This shows how rich how this plant material can be and also reveals the hidden potentials inherent in it. This could be used to supplement diets and meet various nutritional and needs of individuals.